Aksi Kamisan: Lamenting Women, State Violence and Human Security - Mutiara Andalas (Parahyangan Center for International Studies, 2017)
This paper investigates the relationship of Aksi Kamisan and human security. It narrates the phenomenon of women participating in Aksi Kamisan who lament silently before the Presidential office. It explores the essential contribution of these women parading in front of the government offices in promoting human security. Women participants of Aksi Kamisan choose lamentation as a persuasive language to deliver messages on the importance of human security. Analyzing their letters sent to the present President and listening to their oral testimonies, I systematize their previously implicit understanding of human security. In the process I expose the underlying theology of the so-called ‘god of security’ by regimes after the reformation era. Finally I reflect on the theme from the historical-feminist-theological perspectives finding deeper meaning in the pursuit of truth and healing in the face of human suffering.